Endothelium-Independent Vasodilatory Effect of Sailuotong (SLT) on Rat Isolated Tail Artery. (22nd September 2020) - Yeon, S. Y.; Seto, S. W.; Chan, G. H. H.; Low, M.; Kiat, H.; Wang, N.; Liu, J.; Chang, D.
Abstract : Background . Sailuotong (SLT) is a standardized three-herb formulation consisting of extracts of Panax ginseng, Ginkgo biloba, and Crocus sativus for the treatment of vascular dementia (VaD). Although SLT has been shown to increase cerebral blood flow, the direct effects of SLT on vascular reactivity have not been explored. This study aims to examine the vasodilatory effects of SLT and the underlying mechanisms in rat isolated tail artery. Methods . Male (250–300 g) Wistar Kyoto (WKY) rat tail artery was isolated for isometric tension measurement. The effects of SLT on the influx of calcium through the cell membrane calcium channels were determined in Ca 2+ -free solution experiments. Results . SLT (0.1–5, 000  μ g/ml) caused a concentration-dependent relaxation in rat isolated tail artery precontracted by phenylephrine. In the contraction experiments, SLT (500, 1, 000, and 5, 000  μ g/mL) significantly inhibited phenylephrine (0.001 to 10  μ M)- and KCl (10–80 mM)-induced contraction, in a concentration-dependent manner. In Ca 2+ -free solution, SLT (500, 1, 000, and 5, 000  μ g/mL) markedly suppressed Ca 2+ -induced (0.001–3 mM) vasoconstriction in a concentration-dependent manner in both phenylephrine (10  μ M) or KCl (80 mM) stimulated tail arteries. L-type calcium channel blocker nifedipine (10  μ M) inhibited PE-induced contraction. Furthermore, SLT significantly reduced phenylephrine-induced transient vasoconstriction in the rat isolated tail artery. Conclusion . SLT induces relaxation of rat isolated tail artery through endothelium-independent mechanisms. The SLT-induced vasodilatation appeared to be jointly meditated by blockages of extracellular Ca 2+ influx via receptor-gated and voltage-gated Ca 2+ channels and inhibition of the release of Ca 2+ from the sarcoplasmic reticulum.